IMPLEMENTASI PASAL 40 AYAT (1) PERATURAN PEMERINTAH NO. 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - poetra, Rahmat rizal (JURNAL HUKUM dan KENOTARIATAN, 2018)
Land is one source of livelihood and livelihood for people and society. The goverment has the responsibility as well the main task to protect the entire nation of indonesia contained in it. All aimed to promote the general welfare educate the life of the nation, and participate in the implementation of world order. So the need for legal certainty in the process of land registration. In the implementation of land registration Official Deed Office (PPAT) and the National Land Agency (BPN) plays an important role. The legal consequences of Land Acquisition Officials (PPAT) are late in submitting the deed namely in the form of administrative sanction and reprimand from the Office of National Land Agency (BPN). So it is necessary to socialize, improve facilities, and more assertive sanctions.